PENGAWASAN USAHA KARAOKE OLEH PEMERINTAH KOTA PEKANBARU TAHUN 2016-2017 - M. Fajar Rachmi Al Dufri; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Lately karaoke has flourished in the city of Pekanbaru and as for the reasons for the rise of this business is established because the entertainment media this one is very affordable both in terms of middle and upper middle class economy and with the many stands this karaoke business will contribute to sufficient regional cash income significant. Besides this karaoke business place is a type of business that requires supervision in the implementation of its business both in terms of its licensing and operational management. In this case the Pekanbaru City Government issued Regional Regulation No. 3 of 2002 concerning General Entertainment, one of which is a karaoke place as a form of efforts to curb the entertainment place.The concept of theory used according to Usman Effendi is the standard setting stage, the measurement phase of the implementation of activities and the stage of taking corrective actions. This research was conducted in the city of Pekanbaru using qualitative descriptive methods, collecting data through observation and interviews with the informants concerned with the research. The purpose of carrying out supervision of this type of entertainment so as not to cause danger, disruption and abuse of functions in the implementation of its operations on the surrounding environment.This supervision is carried out by several related institutions, namely the Investment Service and One Stop Services of Pekanbaru City, Pekanbaru City Culture and Tourism Office and actors in the Pekanbaru City Civil Service Police Unit assisted by the Riau Provincial Police. From the results of this study it is known that the ongoing supervision has not run well and effectively. This is because there are still entertainment places that do not comply with the applicable regulations and have been determined by the Pekanbaru City Government. The violations still often occur due to the lack of strict sanctions from the Pekanbaru City Government in carrying out the action and the involvement of several individuals in the practice of rent seeking towards business managers that causes supervision to not run optimally.Keywords : Monitoring